Beyond the "core-gamer": Genre preferences and gratifications in computer games. (March 2015) - Scharkow, Michael; Festl, Ruth; Vogelgesang, Jens; Quandt, Thorsten
Highlights: We examine the relationship between gaming gratifications and genre preferences. We develop and test a valid measure of gaming gratifications. Game mechanics and narration are the most important gaming gratifications. Players are more motivated by ego-centered gratifications than by social gratifications. The core genres roleplaying and action games are best predicted by gratifications. Abstract: Computer games can be regarded as mainstream media and one of the driving forces in today's entertainment industry. With the recent changes in the field, we also witness an expansion in genres and user groups. A seemingly basic question gains new relevance in light of the growing diversification: Why do people turn to various types of computer games? In this study, we examine the relationship between gaming gratifications and genre preferences on the basis of a multivariate model deduced from previous research. We applied this model to survey data from a representative sample of 4500 gamers. We found that, apart from socio-demographics, individual and content-related gratifications are relevant predictors for genre preferences, especially for "core-gamer" genres such as roleplaying or action and shooter games. Beyond the "core-gamer", there is large group of (older) casual players who prefer puzzle and simulation games and seek fewer and different gratifications from computer gaming.